Konsep Pendidikan Kewirausahaan di Perguruan Tinggi - Rijal Assidiq Mulyana; Aulia Solichah Iman Nurchotimah; Zaenal Mutaqin (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2022)
Entrepreneurship has become an important discourse in the economic development of the nation and state, many academic works that study entrepreneurship and its development in universities. This paper offers the concept of entrepreneurship education in universities which contains material substance and entrepreneurial competence, consists of 5 theme learning; 1. entrepreneurial potential of students. 2. Entrepreneurial character and attitude, 3. Leadership and communication, 4. Business management, 5. Marketing, these 5 subjects are arranged in sub-topics are set out in 14 learning sessions. The models and method teaching and learning that are; 1. Internships, 2. Cooperative learning, 3. Discussion methods, 4. Problem-based learning, 5. Project-based learning, 6. Contextual and teaching learning, 7. Discovery learning, 8. Simulation. This research was conducted with in-depth literature study with entrepreneurship education.